Financial institutions, markets, and money - Kidwell, David S.; Blackwell, David W.; Whidbee, David A.; Peterson, Richard L. (Hoboken, NJ : Wiley & Sons, 2006)
The book written with a strong historical perspective. Throughout the book we give attention to the historical development of financial institutions and markets and discuss important historical events.
Includes bibliographical references and index.
aug 28/05/13
Loans
Keywords: Finance; Financial institutions; Banks and banking; Monetary policy